Wear Rate of Natural Fibre: Long Kenaf Composite - Nordin, Nor Amalina; Yussof, Fauziah Md; Kasolang, Salmiah; Salleh, Zuraidah; Ahmad, Mohamad Ali (Procedia engineering, 2013)
This paper presents an experimental investigation on the specific wear rate between Kenaf Polyester Composite (KPEC) and Kenaf Epoxy Composite (KEC). The raw material used in the present work was long kenaf fiber. The epoxy resin and unsaturated polyester were mixed with hardener at weight ratios of 3:1 and 10:1, respectively. The wear test was carried out using an Abrasion Resistance Tester (TR-600) in dry sliding conditions at a constant velocity of 1.4 m/s. The test was conducted at room temperature with different applied loads ranging from 5 and 30N. It was observed that the wear characteristic of KPEC is comparative to KEC composite material. Both sample materials tested exhibited the same amount of specific wear rate at the certain distance.